2008
DOI: 10.1111/j.1755-618x.2008.00013.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Community Factors Affecting Psychological Sense of Community, Attraction, and Neighboring in Rural Communities*

Abstract: One thousand nine hundred ninety-five individuals in 20 rural Canadian communities were measured on perceived social cohesion by the three Buckner scale subdimensions: psychological sense of community (PSOC), attraction, and neighboring. Number of household children, income over $20,000, age, birthplace in, and years lived in the community significantly positively influenced PSOC and Attraction. Number of household children (positive for income over $20,000; otherwise negative), income over $40,000, birthplace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 38 publications
2
18
2
Order By: Relevance
“…Measures of social bonding adapted from Kyle, Mowen and Tarrant (2004) and sense of community adapted from Wilkinson (2008) were included in the survey as the social bonding dimension as they best reflected the sentiments expressed in the qualitative study. Items were developed for the affect-based everybody's happy from the results of the preceding qualitative work and were phrased to capture the perception of enjoyment of the travel group.…”
Section: Survey Development and Designmentioning
confidence: 99%
“…Measures of social bonding adapted from Kyle, Mowen and Tarrant (2004) and sense of community adapted from Wilkinson (2008) were included in the survey as the social bonding dimension as they best reflected the sentiments expressed in the qualitative study. Items were developed for the affect-based everybody's happy from the results of the preceding qualitative work and were phrased to capture the perception of enjoyment of the travel group.…”
Section: Survey Development and Designmentioning
confidence: 99%
“…This finding may suggest that the relationship between residential stability and social cohesion is strengthened by neighbourhood characteristics such as the adequacy of services and security in the neighbourhood. As indicated in prior studies, length of residence enables social relationships to develop and strengthens community attachment (Bridge 1994;Goudy 1990;Sampson 1988Sampson , 1991, leading in turn to higher levels of social cohesion (Wilkinson 2008). However, to allow residential stability among older people, there is an increasing need for governments to invest in appropriate and affordable long-term housing (Davey 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies conducted among populations of all ages provide some insight, reporting higher levels of social cohesion among married (Farrell et al 2003;Pampalon et al 2007), older (Ellaway et al 2001;Letki 2008;Pampalon et al 2007;Skjaeveland & Garling 1997;Wilkinson 2008) and more highly educated (Buckner 1988;Pampalon et al 2007;Robinson & Wilkinson 1995) people. For the population at large, research has consistently shown that residential stability exerts a positive influence on social cohesion (Buckner 1988;DiPasquale & Glaeser 1999;Ellaway et al 2001;Robinson & Wilkinson 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The items to measure place identity and place dependence were those developed by Williams and Roggenbuck (1989), which have been validated and used in a numerous place attachment studies (Kyle, Graefe, & Manning, 2004, 2005Kyle, Mowen, & Tarrant, 2004;Warzecha & Lime, 2001;Williams & Vaske, 2003 ). The items for social bonding were derived from Kyle, Mowen, and Tarrant (2004) and Wilkinson (2008) to reflect the community feel and friendship aspects described by respondents during the qualitative study of place meanings at Ningaloo (Tonge, 2012).…”
Section: Survey Development and Distributionmentioning
confidence: 99%